Bilingual, Intergenerational Worship and Ministry for Unity - Yu, John (Religions, 2022)
Many Korean American churches have several different worship services on a given Sunday that cater to different age and language groups. The intent is to cater to the different needs of each group, where each group can worship in an age-appropriate setting with the language they are comfortable with. However, it has also had the unintended consequence of creating factions and divisions within the church. It is not uncommon to hear about conflicts and quarrels between Korean Ministry (KM) and English Ministry (EM), from the leadership level down to the congregation members. While there may be several other contributing factors to church conflicts, one key reason is worshipping separately, which creates different spiritual identities within the church. This article proposes that through a creative and engaging bilingual, intergenerational worship and ministry, different generations in Korean American churches, and perhaps other immigrant churches in multilingual and multicultural settings, can worship and learn together as one community with a common spiritual identity. Careful planning of liturgy that is meaningful to different age and language groups is the key. A project conducted at True Light Community Church, a Korean American congregation in the Metro-Denver area, shows that different generations can be brought together in unity as they worship together regularly. In this project, basic qualitative research tools were used to plan a six-month worship and ministry program. The results show that while it is difficult to provide a meaningful, spiritual experience for every single person or generation, bilingual, intergenerational worship and ministry can bring different generations together.